The criminalization of European cartel enforcement : theoretical, legal, and practical challenges - Whelan, Peter (Lawyer) (Oxford : Oxford University Press, 2014)
The challenges facing the criminalisation of cartel activity in the European Union are threefold: theoretical, legal, and practical. This book analyses these crucial challenges so that the complexity of the process of European antitrust criminalisation can be accurately understood.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on October 28, 2014).
Keywords: Antitrust law -- Europe; Cartels -- Europe